2022
DOI: 10.1001/jamapsychiatry.2022.1256
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Suicide and Nonsuicidal Self-injury in Children

Abstract: IMPORTANCEConsiderably less is known about self-injurious thoughts and behaviors (SITBs) in preadolescence than older age groups, owing partly to the common view that young children are incapable of suicidal thoughts. Yet, preadolescent suicide has increased in recent years and is now the fifth leading cause of death in this age group, leading the National Institute of Mental Health to identify it as a priority for research and intervention.OBJECTIVE To assess prevalence estimates of preadolescent SITBs, ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(71 citation statements)
references
References 94 publications
6
61
0
4
Order By: Relevance
“…A study conducted in 11 European countries among adolescents showed overall lifetime prevalence of self-injury was 27.6% ( 5 ). A meta-analysis including 626 million individuals showed the lifetime prevalence of non-suicidal self-injury among preadolescents were 6.2% in community samples ( 6 ). In China, a nationwide survey ( n = 1,908) in rural area showed 12.2% of adolescents met the suggested DSM-5 criteria for NSSI ( 7 ); and a meta-analysis ( n = 160,348) showed the prevalence of non-suicidal self-injury was 14.5% in middle school and high school students ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in 11 European countries among adolescents showed overall lifetime prevalence of self-injury was 27.6% ( 5 ). A meta-analysis including 626 million individuals showed the lifetime prevalence of non-suicidal self-injury among preadolescents were 6.2% in community samples ( 6 ). In China, a nationwide survey ( n = 1,908) in rural area showed 12.2% of adolescents met the suggested DSM-5 criteria for NSSI ( 7 ); and a meta-analysis ( n = 160,348) showed the prevalence of non-suicidal self-injury was 14.5% in middle school and high school students ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…This age group has received little attention and seems to be a phenomenon separate from adolescent suicide, with different epidemiology and requiring specific assessment and prevention strategies. In recent meta-analyses, the pooled estimated lifetime prevalence of suicidal ideation was 10–15% (6% within the past 12 months), of suicide attempts was 1.5–2.6%, and of nonsuicidal self-injury was 6.2% in children [20 ▪▪ ,21]. Significant correlates of child suicidal thoughts and behaviors are depression, maltreatment, and low parental support [20 ▪▪ ].…”
Section: Epidemiological Trends and Specific Risk Groupsmentioning
confidence: 99%
“…In recent meta-analyses, the pooled estimated lifetime prevalence of suicidal ideation was 10–15% (6% within the past 12 months), of suicide attempts was 1.5–2.6%, and of nonsuicidal self-injury was 6.2% in children [20 ▪▪ ,21]. Significant correlates of child suicidal thoughts and behaviors are depression, maltreatment, and low parental support [20 ▪▪ ]. Of specific concern are children of color, those living in poverty, and those experiencing sexual and physical abuse [22 ▪ ,23].…”
Section: Epidemiological Trends and Specific Risk Groupsmentioning
confidence: 99%
“…Suizid findet sich – bei steigender Tendenz – in vielen Industriestaaten bei Jugendlichen unter den 5 häufigsten Todesursachen. Eine in JAMA Psychiatry publizierte Metaanalyse aus den USA [ 2 ] beschreibt nun die Häufigkeit suizidaler Gedanken, von Suizidversuchen und nichtsuizidaler Selbstverletzung in der Präadoleszenz (Alter unter 13 Jahren). Für die Analyse wurden 58 Studien herangezogen, die insgesamt über 626 Mio.…”
Section: Suizidgedanken Und Selbstverletzung In Der Präadoleszenzunclassified